Respuesta :

DeanR

For system 5. we multiply the first equation by -1

-2g - 3h + 8j = -10

The third equation is

-2g - 3h + 8j = 5

They both can't be true.  

Answer: NO SOLUTIONS

8.

We can eliminate z by multiplying the third equation by 2 and adding to the first:

2x - 10y - 4z = -8

2x + 3y + 4z = 2

Adding,

4x - 7y = -6

Let's eliminate z from the second by multiplying it by 2, the third by 3, and adding.

10x - 4y + 6z = 0

3x - 15y - 6z = -12

13 x - 19 y = -12

Ok, we eliminate y by muliplying our first x,y equation by 19, the last by 7, and subtracting

4(19)x - 7(19)y = -6(19)

13(7)x - 19(7)y = -12(7)

(4(19) - 13(7)) x = -6(19)+12(7)

x = ( -6(19)+12(7)) / (4(19) - 13(7)) = 2

That worked out.

7y = 4x + 6 = 4(2) + 6 = 14

y = 2

4z = 2 - 2x - 3y = 2 - 2(2) - 3(2) = 2 - 4 - 6 = -8

z = -2

Answer: x=2, y=2, z=-2

Check:

2(2)+3(2)+4(-2) = 2 good

5(2) - 2(2) + 3(-2) = 0 good

2 - 5(2) - 2(-2) = -4 good